Potts anastomosis in children with severe pulmonary arterial hypertension and atrial septal defect - Alice Capel (ESC Heart Failure, 2021)
Abstract Aims Potts shunt has been proposed as a bridge or alternative to lung transplantation for children with severe and drug‐refractory suprasystemic pulmonary arterial hypertension (PAH). We describe the management of the atrial shunt when a Potts shunt is planned in refractory PAH. Methods and results We report a case series of children in whom a Potts shunt was done for severe PAH associated with an atrial septal defect to illustrate the different clinical and haemodynamic scenarios. Five children (2 to 13 years) underwent a Potts shunt: three surgical, one percutaneous Potts shunt, and one percutaneous stenting of a restrictive arterial duct. All had associated atrial septal defect. Those who had generalized cyanosis before the procedure had a complicated postoperative course and required longer ventilatory and inotropic support, except the one who had atrial septal defect closure before the Potts shunt. One of the three cyanotic patients died. Two patients with left‐to‐right shunt before the Potts shunt had an uncomplicated postoperative course. Conclusions Shunt physiology is only partially predictable after the Potts shunt in children with PAH and atrial septal defect. Abrupt drop in left ventricle preload while the right ventricle is decompressed can potentially be prevented by atrial septal defect closure prior to the Potts shunt.